2016
DOI: 10.1016/j.annepidem.2016.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Relation of longitudinal changes in body mass index with atherosclerotic cardiovascular disease risk scores in middle-aged black and white adults: the Coronary Artery Risk Development in Young Adults (CARDIA) Study

Abstract: PURPOSE We assessed whether longitudinal changes in body mass index (BMI) is positively associated with changes in 10-year AHA/ACC atherosclerotic cardiovascular disease (ASCVD) risk scores in middle-aged blacks compared to whites. METHODS Data were from 1,691 participants enrolled in CARDIA aged ≥40 years in 2000–2001, who had follow-up exams 5 and 10 years later. RESULTS The prevalence of obesity increased from 32.3% in 2000–2001(mean age: 42.8 years) to 41.7% in 2010–2011, higher in blacks than whites. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Furthermore, a study with an international cohort showed that CVD risk in obese and overweight people was not higher than those with normal BMI, and a reverse J-shaped curve persisted between BMI category and incidence of CVD outcomes (31). A longitudinal study in the United States showed that BMI had little independent influence (0.07% per 1 kg/m2 increase) on 10-year atherosclerotic CVD risk scores (32). A systematic review of 40 cohort studies found that overweight and obese people had better survival and lower CVD events (33).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a study with an international cohort showed that CVD risk in obese and overweight people was not higher than those with normal BMI, and a reverse J-shaped curve persisted between BMI category and incidence of CVD outcomes (31). A longitudinal study in the United States showed that BMI had little independent influence (0.07% per 1 kg/m2 increase) on 10-year atherosclerotic CVD risk scores (32). A systematic review of 40 cohort studies found that overweight and obese people had better survival and lower CVD events (33).…”
Section: Discussionmentioning
confidence: 99%
“…Data from 1691 participants enrolled in the Coronary Artery Risk Development in Young Adults Study aged 40 years or more showed that in middle-aged adults, longitudinal changes in BMI had the little independent influence on changes in 10-year atherosclerotic cardiovascular disease risk scores as its effect may be largely mediated through risk factors already accounted for in the risk score. [ 20 ] WHtR indices could differ among sex and age groups because whole-body fat distribution and WC change considerably with age and also height differs among generations. [ 21 ] Two previous studies, in the United States and China, reported that the association between WHtR and cardiovascular disease was stronger among younger adults as compared with elderly adults.…”
Section: Discussionmentioning
confidence: 99%
“…Four (10.0%) studies modelled changes in risk scores over time using linear mixed effects (LME) models, [ 33 , 44 , 46 ] for example, predicting the trajectory of the Framingham Risk Score over four time-points [ 44 ]. Fixed effects linear regression was used by one study [ 52 ] to examine how change in body mass index (BMI) is correlated with the Framingham Risk Score.…”
Section: Resultsmentioning
confidence: 99%